1998
DOI: 10.2214/ajr.171.6.9843300
|View full text |Cite
|
Sign up to set email alerts
|

Decidualized ovarian endometriosis mimicking malignancy.

Abstract: Becausesonography is nowcapable of achieving increased resolution, ovarian tumors are more fre quently found in early pregnancy. In this case, we describea patientin the secondtrimester with ovarian endometriosis, which enlarged and was accompanied by structural changes inside the tumor. Case ReportA 28-year-old primigravidawas first seen in our antenatal clinic at 5 weeks of gestation. She had a history ofovarian endometriosis and had been treated with a gonadotropin-releasing hormone analogue before the preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 1 publication
2
40
0
2
Order By: Relevance
“…Decidualization occurs not only in the uterine but also in the extrauterine endometrium during pregnancy [1,4,6] , especially in endometrial stromal cells of ovarian endometriotic cysts [1,4] . This study revealed that decidualized ovarian endometriotic cysts showed papillary excrescences mimicking malignancy during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decidualization occurs not only in the uterine but also in the extrauterine endometrium during pregnancy [1,4,6] , especially in endometrial stromal cells of ovarian endometriotic cysts [1,4] . This study revealed that decidualized ovarian endometriotic cysts showed papillary excrescences mimicking malignancy during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon also occurred in histologically confirmed ovarian endometriotic cysts without preoperative ultrasound/MRI findings; however, no previous reports have described it. Although to our knowledge, 6 cases were hitherto reported in which decidualized ovarian endometriotic cysts showed ultrasound features mimicking malignancy, necessitating surgery during pregnancy [1][2][3][4][5] ( table 1 ), the clinical features such as MRI findings, Doppler findings, or the serum CA125 level, were not fully described in some cases. The present report adds 3 further cases with detailed descriptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all the enhanced ovarian lesions are malignant (12,13). Some benign lesions also have contrast enhancement effect; for instance, polypoid endometriosis (14), decidualized endometriotic cysts during pregnancy in endometriosis (15) or even normal endometriotic tissue itself (12), mature cystic teratoma (13), and many sex cordstromal tumors (1,16). Although we did not evaluate if the PF contributed to the differentiation between malignant and benign tissues, knowing if a lesion has blood supply will be helpful in their characterization.…”
Section: Discussionmentioning
confidence: 99%
“…One of the difficulties in diagnosing malignancy in endometriosis is a decidualized endometriosis during pregnancy, which presents as a rapidly growing nodular portion or wall thickening with abundant vascularity in the endometriotic cyst. This finding can be easily misdiagnosed as a malignancy [10][11][12]. In such cases, expectant management with careful serial follow-up is needed.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%